Has the implementation of the TRIPS Agreement in Latin America and the Caribbean produced intellectual property legislation that favours public health? - Maria Auxiliadora Oliveira; Jorge Antonio Zepeda Bermudez; Gabriela Costa Chaves; Germán Velásquez
OBJECTIVE: The World Trade Organization's Trade-Related Aspects of Intellectual Property Rights (TRIPS) Agreement establishes minimum standards for intellectual property rights, including patent protection for pharmaceuticals; therefore, it may make it difficult for developing countries to gain access to medicines, especially those countries that are the least developed. This study aims to determine whether implementation of the TRIPS Agreement in Latin American and Caribbean countries has generated patent legislation that is sensitive to public health needs. METHODS: Legislation in 11 Latin American and Caribbean countries was analysed. The variables considered in the analysis were: the term of patents issued, patentable subject matter, transition periods (that is, time until legislation was enacted), reversal of the burden of proof of patent infringement, exhaustion of rights, compulsory licensing and the early working exception (which allows a country to complete all procedures necessary to register a generic product before the original patent expires). FINDINGS: By 2000, all of the countries studied had reformed their legislation to conform to the agreement. Brazil and Argentina used the transition period until 2005 to grant patents in the pharmaceutical industry. All countries, except Panama, made use of the safeguards and flexibilities available through the agreement by including mechanisms for compulsory licensing in their legislation. Argentina; Bolivia, Colombia, Ecuador, Peru and Venezuela (countries that represented the Andean community); the Dominican Republic; and Panama included mechanisms to allow parallel importation. Mexico did not. Brazil only permits parallel importation after a compulsory licence has been issued. The early working exception is included in legislation in Brazil and the Dominican Republic. CONCLUSION: The countries in this study did not incorporate all of the mechanisms allowed for by the Agreement and are not adequately using the provisions that enable World Trade Organization (WTO) members to obtain better health for the public, particularly in regard to gaining access to medicines. This situation may deteriorate in future if other agreements establish more restrictive rules for intellectual property rights.